MINERALIZATION STUDY OF RADIOACTIVE MINERALS IN MAMUJU, WEST SULAWESI - RAKHMA (NIM: 22012009), ERSINA
Mamuju become a study area based on environment monitoring conducted by Center For Safety Technology and Radiation Metrology, National Nuclear Energy Agency (PTKMR BATAN) specifically measuring activity of gamma radiation dose rate in Sulawesi Island. This study indicated a high radiation dose rate of environment (100-2800 nSv/hour) and exceeded limit of radiation dose rate for people society, namely 0.3 mSv/year or 34.25 nSv/hour. Since exploration conducted in Sulawesi did not involve Mamuju area’s therefore mineralization of radioactive minerals in Mamuju is undeterminated. The methodology used is geochemical dan mineralogical analysis. Geochemical analysis is perfomed using X-Ray Flourescence (XRF), whereas mineralogical analysis is conducted by megascopically observation of rocks and thin section (petrography analysis). Rock samples are taken from Adang Volcanic Rock Formation which composed by tuff, lava and volcanic breccia, particularly Leucite-Basalt composition. SiO2-K2O diagram presents magmatic affinity shoshonitic to ultrapotassic in Mamuju. Determination of U and Th anomaly threshold using probability curve. Anomaly threshold of U was 237.14 ppm which widespread in Salunangka, Botteng, Takandeang, Saleto, Pengasaan, Taan, Tande-tande and Hulu Mamuju. Whereas anomaly threshold of Th was 1258,93 ppm merely in Hulu Mamuju area. Determination element association of U and Th using Pearson correlation coefficient and percentile methods. Based on the association of U and Th, Mamuju area has “epithermal” precious metal type deposits. Characteristic of volcanic products in Mamuju were within plate dan arc related volcanism corresponding with tectonic of Mamuju which was developed from subduction to collision. Distribution of U and Th in Mamuju were not constanly linear, random enrichment in each element and not correlative which presented element distributions in continent crust (in Mamuju) were unequal. Th anomaly in Hulu Mamuju may related with hydrothermal process which through part of Th-rich crust with less U contain, therefore Th anomaly was formed with low grade U. Furthermore, hydrothermal process may dissolving mobile radioactive element (U) and leaving immobile radioactive element (Th).